Modification of hydrothermal synthesis using microwave irradiation for ZnO/graphene nanocomposite. Issue 2 (June 2021) - Sugianto,; Rahayu, E F
Abstract: Graphene has good physical properties such as electronic, optical and mechanical properties. The unique properties of graphene are interesting to study, especially in the field of electronic devices. Graphene was synthesised with chemical reduction using the Tour method. The oxidation process of graphite into graphene oxide (GO) occurs in a solution with the acidic atmosphere of H2 SO4 /H3 PO4 . ZnO/graphene nanocomposite was prepared by modification of hydrothermal synthesis using microwave irradiation. Characterisation of material structures includes SEM-EDX and FTIR. SEM micrograph shows that the morphology of the ZnO/graphene synthesis of oxidising acids H2 SO4 /H3 PO4 9:1 ratio has better performance.